Implementing the Readiness of Key Audit Matters at Division X KAP ABC - Rahcoyoning Widianingrum; Nureni Wijayati (International Journal Labs, 2022)
Users of financial statements may have higher expectations due to audit reports, which are thought to be of no informational value. Including essential information in the audit report will decide how it can be used because the